Distribution Route Optimization Using Nearest Neighbor Algorithm and Clarke and Wright Savings - Pratiwi, Miftah; Lubis, Riri Syafitri (Sinkron : jurnal dan penelitian teknik informatika, 2023)
in the process of this research Problems that occur is an irregular delivery of goods that takes a lot of time and delivery distance, so the distribution delivery process is not optimal. Therefore, researchers will conduct research on how to determine the best distribution route in optimizing delivery distance and time. The purpose of this study is to find distribution routes that are more optimal by using the nearest neighbor and Clarke and Wright savings and do a comparison with the company's current route This. The company's current mileage route is 319.9 km while using the nearest neighbor algorithm, the total distance traveled so far is obtained 240.9 and experienced mileage savings of 79 km or 25.22% and with the Clarke and Wright savings algorithm, the distance traveled is obtained 239.2 km and experienced mileage savings of 80.7 km or 25.22 %. Therefore, the Clarke and Wright Savings algorithm is more